Effects of cattle manure compost application on crop growth and soil-to-crop transfer of cesium in a physically radionuclide-decontaminated field - Suzuki, Masataka; Kubo, Katashi; Hachinohe, Mayumi; Sato, Takashi; Tsukada, Hirofumi; Yamaguchi, Noriko; Watanabe, Toshihiro; Maruyama, Hayato; Shinano, Takuro (Science of The Total Environment, 2024)
Resuming crop production in physically decontaminated fields affected by radiocesium (134Cs and 137Cs) releases is crucial for restoring impacted areas. However, surface soil excavation to reduce radiocesium may lead to lower crop yield due to the loss of fertile topsoil. This study aimed to assess the effects of cattle manure compost (CMC) application on soil properties, crop growth, and 137Cs soil-to-crop transfer in a physically decontaminated field and pot experiment. Field trials were conducted during 2018–2022, with CMC (1 and 2 kg m−2 year−1) applied alongside conventional fertilization (CMC1 and CMC2 plots, respectively) in 2018–2019 and conventional fertilization alone in 2020–2022. Additionally, a pot experiment was used to evaluate the impact of CMC application in soil (1 kg m−2 year−1 for 5 years) on 137Cs transfer. In the field trial during 2018–2019, CMC1 and CMC2 plots exhibited higher soybean shoot dry weight (DW) compared with plots receiving conventional fertilization and additional K fertilizer (+K2O). CMC application also improved soil nutrient content. The transfer factor of 137Cs (TF-137Cs: plant 137Cs activity concentration/soil 137Cs activity concentration) followed the order CMC2 < CMC1 ≈ +K2O < conventional fertilization only (CF) and was negatively correlated with soil exchangeable K (Ex-K). During 2020–2022, when all plots received conventional fertilization alone, grain yields were higher in CMC1 and CMC2 plots than in the +K2O plot, with the lowest TF-137Cs in CMC2 plot followed by CMC1, +K2O, and CF plots. The pot experiment confirmed that CMC soil had a lower TF-137Cs and higher plant DW compared with CF soil with the same Ex-K level. Additionally, the soil exchangeable 137Cs (Ex-137Cs) level was significantly lower in CMC soil than CF soil. These findings demonstrate the potential of CMC application to improve crop growth and reduce 137Cs transfer in physically decontaminated fields. [Display omitted] •The decontaminated fields have problems with reduced soil fertility and radiocesium residues.•Cattle manure compost application to the decontaminated fields increased the various soil nutrients.•Cattle manure compost application enhanced crop growth and yield in the decontaminated fields.•Cattle manure compost application reduced the transfer of radiocesium from soil to crop.•The application of cattle manure compost promoted the fixation of radiocesium in the soil.